ANALISIS STRUKTUR PERKERASAN RUNWAY, TAXIWAY DAN APRON BANDAR UDARA DR. F.L. TOBING MENGGUNAKAN METODE UNITED STATES OF AMERICAN PRACTICE - utama, dwinanta (Badan Pengkajian dan Penerapan Teknologi, 2006)
Airport is the point of interchange between people or cargo to transfer from air transportation system to other system of transport such as land and water transportation system. Airport is also a facility for supporting fast and long distance transportation such as inter-cities or inter-island transportation system. Currently many Kabupaten/Kota in Indonesia eager to improve their existing airport since the era of otonomi daerah started, to generate and accelerate regional development. Consequently the airport improvement should include not only landside but also the airside facilities such as runway, taxiway and apron.Runway, taxiway and apron pavement structure are sometime designed in various methods. One method that is recently implemented in Indonesia is the United Stage of American Practice method, recommended by International Civil Aviation Organization (ICAO). This analysis shows the strategy to develop the airside facilities and to design the runway, taxiway and apron pavement structure using that method. The development plan of DR. F.L. Tobing, Sibolga airport in Kabupaten Tapanuli Tengah, North Sumatera Province will be used as the case study. There are three phases in this development plan to determine the airside facilities. The aircraft to be used in the future are F-28 in phase I (2003-2012), F-100 in phase II (2012-2022) and B-737 in Ultimate Phase (After 2022).